The Internationalization of Companies: Structural Comparison Analysis between Behavioral Models and Economic Models - Maioui, Mohamed Noor; Gassemi, Karim (International Review of Management and Marketing, 2021)
A large number of theoretical publications and empirical studies are devoted to the analysis of the internationalization of companies. Many conceptual frameworks have been adopted to understand this phenomenon. The internationalization of enterprises is a field of research that has shaped several developments in the last decade. Several authors have developed different models with the objective of analyzing factors of international development. This article deals with a literature review of the main models of internationalization. Two typologies of models are analyzed. Models qualified as behavioral and models qualified as Economics. Keywords: Internalization, Economic model, Behavioral model, comparative analysis. JEL Classifications: F11, F20, F21, F2 DOI: https://doi.org/10.32479/irmm.11038